2019
DOI: 10.1590/1806-9282.65.9.1193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the protective effect of enoxaparin and ticagrelor pretreatment against ischemia-reperfusion injury in rat lung tissue

Abstract: SUMMARY OBJECTIVES This study was conducted to reveal the possible protective effects of ticagrelor and enoxaparin pretreatment against ischemia-reperfusion (IR)-induced injury on the lung tissue of a rat model. METHODS Wistar albino rats were randomly divided into 4 groups as follows: group-1 (control-sham), group-2 (control-saline+IR), group-3 (ticagrelor+IR), group-4 (enoxaparin+IR). Before the ischemic period, saline, ticagrelor, and enoxaparin were administered to the 2nd-4th groups, respectively. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Lung ischaemia-reperfusion injury (LIRI), known as a frequent and severe clinical complication, has a high mortality after lung transplantation worldwide (80,81). LIRI is a pathological process with the clinical feature of initial restriction of blood supply to lung organs followed by the restoration of perfusion, which involves oxidative stress (82).…”
Section: Mt and Lirimentioning
confidence: 99%
“…Lung ischaemia-reperfusion injury (LIRI), known as a frequent and severe clinical complication, has a high mortality after lung transplantation worldwide (80,81). LIRI is a pathological process with the clinical feature of initial restriction of blood supply to lung organs followed by the restoration of perfusion, which involves oxidative stress (82).…”
Section: Mt and Lirimentioning
confidence: 99%
“…The approximate percentage of apoptotic cells was estimated based on 10 representative fields in each section. The immunostaining intensity was scored as negative (−), very weak (1+), moderate (2), strong (3+), and very strong (4+) [7][8][9][10] .…”
Section: Caspase-3 Immunohistochemistrymentioning
confidence: 99%
“…Group 1 was not treated. Before the ischemic period, Group 2 received 0.1 mL/kg saline, Group 3 received 25 mg/kg ticagrelor (Brilinta, AstraZeneca, Södertalje, Sweden) via gastric gavage while Group 4 received 0.75 mg/kg enoxaparin (Clexane, Sanofi Winthrop Industrie, Maisons-Alfort, France) subcutaneously 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ticagrelor might reduce infection occurrences in the clinic, especially for pneumonia ( Li et al, 2021 ; Storey et al, 2014 ; Varenhorst et al, 2012 ). Furthermore, ticagrelor alleviates ALI and/or inflammation in vivo against infections, including abdominal sepsis and pneumonia, and in response to myocardial ischemia-reperfusion injury ( Fındık et al, 2019 ; Lancellotti et al, 2019 ; Rahman et al, 2014 ). Ticagrelor inhibits several pyroptosis-associated proteins, including NLRP3, adaptor protein apoptosis-associated speck-like protein containing a caspase recruitment domain (CARD) (ASC), and caspase-1 in cells as well as several experimental models ( Birnbaum et al, 2016 ; Chen et al, 2020 ; Huang et al, 2020 ; Penna et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%